Advection - diffusion model for indoor-outdoor exchange of air pollutants from electric power generators servicing buildings. Issue 1 (31st December 2022) - Akintola, Olumuyiwa; Sonibare, Jacob
Abstract: This study developed mathematical modeling equations for the interactions between outdoor electric power generator air emissions and indoor receptors location. It also describes a numerical solution for the transportation of air pollutants in a simple rectangular box domain. The mathematical model of indoor pollution from electric power generators operated near buildings using one-dimension advection and one-dimension diffusion was solved numerically. The finite difference method was used in solving the model with respect to advection term only, diffusion term only and both advection and diffusion terms. The numerical solution of this equation were obtained using the Crank-Nicolson scheme and by implementing the numerical scheme via developing computer programming codes of Crank-Nicolson scheme for advection and/or diffusion equation. The results from the concentration profiles of advection term only and diffusion term only show that the concentrations of air pollutants decrease with time and remains constant at a point, this differs when both terms are considered together. Finally, governing equations with solution of concentrations varying with time and space can be established for air emissions from outdoor electric power generators operated near buildings with their associated effects on indoor air quality.